When Social Responsibility Trascends Differences: Interactivity, Customer Co-Creation, and Perceived Value during a Boycott - Hapsari, Nurul Retno; Sagita, Virginia Ayu; Abadi, Medi Trilaksono Dwi; Dewanti, Ida Susi; Wijayanti, Dewi Mukti (Jurnal Paradigma, 2026)
Interactivity in corporate social responsibility (CSR) is a significant catalyst for customer involvement, however, its role in sustaining brand value under socio-political pressure, such as boycott movements and across religious groups remains underexplored. This study examines the impact of perceived CSR interactivity on customer brand co-creation behavior (CBCB) and perceived value in the context of the Boycott, Divestment, and Sanctions (BDS) movement against Starbucks, while assessing potential differences between Muslim and Christian consumers. A quantitative approach was applied using PLS-SEM to test direct and indirect effects, alongside Multi-Group Analysis (MGA) to evaluate cross-religious responses. Data were collected from 110 Starbucks customers through online surveys using non-probability sampling. The result indicate that perceived CSR interactivity positively CBCB, which in turn enhances perceived value, confirming the mediating role of co-creation behavior. MGA reveals no significant differences between Muslim and Christian customers, suggesting that interactive CSR grounded in universal social values operates consistently across religious groups. Theoretically, this study extends Service-Dominant Logic by demonstrating that value co-creation through interactive CSR remains effective in crisis context characterized by boycott pressure. Businesses are therefore encouraged to design inclusive and interactive CSR initiatives to strengthen customer engagement and sustain brand value during reputational challenges.